COVID-19 and Idiosyncratic Food Dearth Risk Resilience in Nigeria. - Idowu Oladeji Ojo (ZBW - Leibniz Information Centre for Economics, 2020)
This study examined the interplay of COVID-19 and Idiosyncratic Food Dearth Risk Resilience in Nigeria; focusing on Oyo State as case study. A multistage sampling technique was used to elicit primary data from 210 rural crop farmers in the study area using a semi-structured questionnaire. CARE and WFP Household Coping Strategy Index (CSI) and Factor analysis were used to determine level of household resilience for food security in the study area. Likert scale was used to examine the idiosyncratic coping strategies adopted by the respondents against food dearth related risks during the COVID-19 Pandemic in Nigeria. Findings showed that 8 out of every 10 respondents do not have access to palliative stimulus packages from the Federal or Oyo state Government to impair the effect of the COVID-19 Pandemic. Out of the sampled households, only 35.71%, 32.38% and 31.90% had mild, moderate and severe resilience for food security respectively during the COVID-19 Pandemic in the study area. Results revealed that the households differ in socio-economic characteristics by their resilience level to food insecurity and that the idiosyncratic coping strategies of households against food dearth related shocks include relying on less preferred food, borrowing food, buying food on credit, allowing household members to eat elsewhere, begging for food, limiting portion of food, and restricting adult at meal. The study concluded that policies that underpin expansion of near-real time food security monitoring systems to provide timely, improved and geospatially indicative data to measure the pandemic's unfolding effects and understand better farmers that are suffering from hunger and malnutrition and where they are. It suggested that food and nutrition assistance needs to be at the heart of Government social protection programs and laying the foundation for a more inclusive, green, and resilient recovery by ensuring COVID-19 dedicated resources are used in a “build to transform” approach and are evidence-based with emphasis on women and children.
Keywords: Q12; Q18; 330; Food Security; Idiosyncratic; COVID-19; Resilience; Nigeria